Education and Training Requirements for Occupations - Scoville, James G. (The Review of Economics and Statistics, 1966)
IN the May, 1964 issue of this REVIEW, R. S. Eckaus presented estimates of general and specific education and training requirements by industry.1 For the analysis of projected demands on the educational system, it may be more useful to have such data on an occupational basis as technological change is not usually conceived of as neutral with respect to the component occupations of an industry. It is the purpose of this article to present such data and examine some of their deficiencies. There are substantial reasons to seek education and training requirements data on an occupational basis. If estimates can be Sbtained of the amounts of various types of training required to fill a certain job, then projections of changing occupational patterns will yield predictions of requirements of the educational and training system. Such predictions could tell us not only what specific occupations to train for, but the amount of teaching time and other costs required to train a work force in the new pattern. Further, educational and training requirements should be related to mobility characteristics of occupations. Presumably a higher level of formal or general education will be associated with a greater degree of occupational mobility, with the reverse probably being true with regard to level of training for a specific job.